The effect of technology on Arabic language learning in higher education - Ritonga, Mahyudin; Mudinillah, Adam; Wasehudin, Wasehudin; Julhadi, Julhadi; Amrina, Amrina; Shidqi, Muhammad Husni (Journal of Education and Learning (EduLearn), 2024)
Technology is advancing and developing, and we cannot let go of our lives. One of them is in the world of education, the use of technology is often found. teachers combine technological devices in the learning process so that the learning atmosphere becomes more interesting, not only with increasingly open technological developments and the spread of information and knowledge throughout the world across the boundaries of space and time. Thus, technological developments have a positive impact on educators and students. In this study, researchers measured the extent to which the application of this technology in the learning process was highly valued. For this reason, this research aims to find out the impact of technology on Arabic language learning at the Batusangkar Institute State Islamic University. The method used in this research is a survey research method. Data collection uses observation, interviews and questionnaires. Furthermore, the expected result of this research is to find out the role or influence of technology on Arabic language learning activities in higher education. Based on the research results, it can be seen that there is an influence or influence of technology on Arabic language learning at the Batusangkar State Islamic Institute.